Optimizing longifolene production in Yarrowia lipolytica via metabolic and protein engineering - Yi-Tong Yao; Xiao Zhang; Chen-Yu Wang; Yu-He Zhang; Da-Wei Li; Wei-Dong Yang; Hong-Ye Li; Li-Gong Zou (Synthetic and Systems Biotechnology)
Longifolene (C15H24) is a tricyclic sesquiterpene widely utilized in the cosmetics and fragrances due to its versatile applications. Traditional extraction methods from plants suffer from low titer and lengthy production cycles, while chemical synthesis is hampered by the compound's complex structure, leading to high costs and insufficient market supply. This study aimed to develop a microbial cell factory for enhanced longifolene production. The strategy involved integrating longifolene synthase from Pinus sylvestris (PsTPS) into Yarrowia lipolytica and employing multiple metabolic engineering approaches. Initially, key genes in the mevalonate (MVA) pathway were overexpressed to enhance longifolene precursor availability for longifolene biosynthesis. Subsequently, protein engineering techniques were applied to optimize PsTPS (tPsTPS) for improved catalytic efficiency. Furthermore, co-expression of molecular chaperones was implemented to enhance the synthesis and secretion of PsTPS. The introduction of the isopentenol utilization pathway (IUP) further augmented the supply of C5 substrate. By optimizing the culture conditions, including a reduction in culture temperature, the efflux of longifolene was increased, and the dissolved oxygen levels were enhanced to promote the growth of the strain. These collective efforts resulted culminated in the engineered strain Z03 achieving a noteworthy production level of 34.67 mg/L of longifolene in shake flasks. This study not only demonstrates the feasibility of enhancing sesquiterpene production in Y. lipolytica but also highlights the potential of microbial platforms in meeting industrial demands for complex natural products.